SKY Castle: Consuming Education from the Cases of Two Tiger Parents - Yuliyanto Chandra (Lingua Cultura, 2020)
The research aimed to analyze how the Korean series, SKY Castle, successfully captured the idea that education could becommoditized in consumer culture for ensuring class mobility, which was majorly done by two exemplary tiger parents inKorea. Methodologically, the research applied a qualitative approach and employed a detailed analysis of the main character and one supporting character, Han Suhjin and Cha Minhyuk, respectively. Both characters’ actions and utterances would be selectively used to support the arguments of the research. Their relationship with other characters would also be used as further explanations. The research sheds light on how the two aforementioned characters fervently pursue and spend millions on education as it is perceived to strengthen their position in the social totem pole. The underlying theories to support the discussion are those of cultural and economic capital, consumption, commodification, and tiger parents. These are interconnected in the Korean context, especially due to the shifting value of education in the contemporary era.